Detecção de anticorpos e pesquisa de DNA de Leptospira spp. e Brucella spp. em bovinos abatidos no Estado do Rio Grande do Norte - Araújo, Kênia Suênia Meira de (2012)
This study was aimed at researching anti-Leptospira spp. and anti-Brucella spp. agglutinins in cattle slaughtered in public slaughterhouses in the State of Rio Grande do Norte, as well as confirm the presence of these agents through PCR in the ovaries and epididymides of the slaughtered animals. For such purpose, serum, and ovary or epididymides were collected from cattle at the public slaughterhouses of that state. Sampling was performed during normal slaughter line, without any interference as the order, sex, age, or origin of the slaughtered animals. The screening of animal reagent to leptospirosis was made through the Microscopic Agglutination Test (MAT). To search for brucellosis, animals were screened by the Buffered Acidified Antigen test (BAA) and as a confirmatory test 2-mercaptoethanol (2-ME) was used. To detect bacterial DNA in samples of ovary and epididymides the Polymerase Chain Reaction (PCR) was used. Of all the 306 animals evaluated, 189 (61.76%) were positive for the MAT, where the predominant serovar was Hardjo (24.9%). The second most frequent serovar was Wolffi (14.8%), followed by Butembo, Icterhaemorrragiae, and Hebdomadis who contributed with frequencies ranging from 6.9% to 2.6%. Lower frequencies were found for the serovars Australis (1.6%), Pomona (1.1%), Grippotyphosa (1.1%) and Patoc (1.1%). Canicola, Autumnalis, and Sentot had frequencies lower than 1%. Three animals were positive for the BAA test, however only one of these reacted positively to 2-ME. Not one of the samples was positive for Brucella spp. and Leptopira spp. DNA through the PCR technique. Given the above mentioned data it was concluded that the Leptospira spp. infection in cattle in the semiarid region of Rio Grande do Norte occurs at higher frequency with the serovar Hardjo during the dry season of the year. The Brucella spp. infection is present but has very low frequency, and no DNA from Leptospira spp. and Brucella spp. was detected in the ovary and epididymis samples of the cattle examined